The Combination of Molecular Hydrogen and Heme Oxygenase 1 Effectively Inhibits Neuropathy Caused by Paclitaxel in Mice - Ignacio Martínez-Martel; Xue Bai; Rebecca Kordikowski; Christie R. A. Leite-Panissi; Olga Pol (MDPI AG, 2024)
Chemotherapy-provoked peripheral neuropathy and its associated affective disorders are important adverse effects in cancer patients, and its treatment is not completely resolved. A recent study reveals a positive interaction between molecular hydrogen (H2) and a heme oxygenase (HO-1) enzyme inducer, cobalt protoporphyrin IX (CoPP), in the inhibition of neuropathic pain provoked by nerve injury. Nevertheless, the efficacy of CoPP co-administered with hydrogen-rich water (HRW) on the allodynia and emotional disorders related to paclitaxel (PTX) administration has not yet been assessed. Using male C57BL/6 mice injected with PTX, we examined the effects of the co-administration of low doses of CoPP and HRW on mechanical and thermal allodynia and anxiodepressive-like behaviors triggered by PTX. Moreover, the impact of this combined treatment on the oxidative stress and inflammation caused by PTX in the amygdala (AMG) and dorsal root ganglia (DRG) were studied. Our results indicated that the antiallodynic actions of the co-administration of CoPP plus HRW are more rapid and higher than those given by each of them when independently administered. This combination inhibited anxiodepressive-like behaviors, the up-regulation of the inflammasome NLRP3 and 4-hydroxynonenal, as well as the high mRNA levels of some inflammatory mediators. This combination also increased the expression of NRF2, HO-1, superoxide dismutase 1, glutathione S-transferase mu 1, and/or the glutamate-cysteine ligase modifier subunit and decreased the protein levels of BACH1 in the DRG and/or AMG. Thus, it shows a positive interaction among HO-1 and H2 systems in controlling PTX-induced neuropathy by modulating inflammation and activating the antioxidant system. This study recommends the co-administration of CoPP plus HRW as an effective treatment for PTX-provoked neuropathy and its linked emotive deficits.